An Enhanced GPS/INS Integrated Navigation System with GPS Observation Expansion. (9th February 2016) - Li, Zengke; Wang, Jian; Gao, Jingxiang
Abstract : In Global Positioning System/Inertial Navigation System (GPS/INS) integrated navigation, the low sampling rate of GPS receivers reduces the observability of state variables. GPS observation expansion is proposed to enhance the GPS/INS integrated navigation system. During the process of observation expansion, the state variables are updated by the same GPS information repeatedly. According to uncertainty theory, the probability density function of GPS observation information is analysed to demonstrate the feasibility of GPS observation expansion. The formula and calculation method of an adaptive filter algorithm are presented to control the uncertainty of GPS observation expansion. Furthermore, an experiment is performed to validate the new algorithm. The results indicate that compared with GPS/INS integrated navigation without observation expansion, the enhanced GPS/INS integrated navigation system can improve the position, velocity and attitude accuracy significantly, especially while a land vehicle is in slow motion. At the same time, the adaptive filter factor is introduced into the new algorithm, which can control the uncertainty caused by the expanded GPS observation.